Environmental Ethics in Agricultural Research Through Vegetation Study of Oil Palm Seedlings - Agustina Matondang; Alfiana Ayu; Alyvia Salsabila; Anisa Anisa; Lydia Siburian; Tania Maulia Hasibuan; Putri Khairani; Aswarina Nasution; Heppy Setya Prima; Eko Prasetya (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
Agriculture is a dominant ecosystem globally in 2023, farmland and pastureland occupied nearly 50 % (about 48 million km2) of habitable terrestrial land. Since the early 2000s, rates of global agricultural expansion have fallen, but agriculture is still expanding rapidly in the tropics. Expansion of tropical agriculture has been driven by a growing human population, increases in per capita consumption rates for agricultural-derived resources, and the high economic value of agriculture in many tropical countries. While tropical agricultural production can increase food security and support human health and livelihoods, conversion of natural tropical habitat to farms and pastures has had severe environmental consequences and changed social dynamics. The research employed a quantitative approach with a case study method. This method was chosen because it provided an opportunity to conduct an in-depth analysis of the application of environmental ethics in agricultural practices and to systematically examine the effects of these ethics on the growth of oil palm seedlings. The application of environmental ethics in agricultural research, particularly in the study of oil palm seedling vegetation, is crucial for achieving sustainability and ecosystem balance. This research demonstrates that sustainable agricultural practices address not only economic outcomes but also social and environmental impacts. In the context of the palm oil industry, the application of ethical principles such as responsibility, intergenerational equity, and community participation is key to addressing issues of deforestation, pollution, and conflict with local communities. The analysis identified challenges in the application of environmental ethics, such as low public awareness and conflicts of interest among stakeholders. However, multi-stakeholder collaboration and enhanced moral education can be a solution to raise awareness and a shared commitment to environmental sustainability